Knockdown of PTGS2 by CRISPR/CAS9 System Designates a New Potential Gene Target for Melanoma Treatment - Giuseppe Ercolano; Paola De Cicco; Valentina Rubino; Valentina Rubino; Giuseppe Terrazzano; Giuseppe Terrazzano; Giuseppina Ruggiero; Roberta Carriero; Paolo Kunderfranco; Angela Ianaro (Frontiers Media S.A., 2019)
CRISPR/Cas9 has become a powerful method to engineer genomes and to activate or to repress genes expression. As such, in cancer research CRISPR/Cas9 technology represents an efficient tool to dissect mechanisms of tumorigenesis and to discover novel targets for drug development. Here, we employed the CRISPR/Cas9 technology for studying the role of prostaglandin-endoperoxide synthase 2 (PTGS2) in melanoma development and progression. Melanoma is the most aggressive form of skin cancer with a median survival of less than 1 year. Although oncogene-targeted drugs and immune checkpoint inhibitors have demonstrated a significant success in improving overall survival in patients, related toxicity and emerging resistance are ongoing challenges. Gene therapy appears to be an appealing option to enhance the efficacy of currently available melanoma therapeutics leading to better patient prognosis. Several gene therapy targets have been identified and have proven to be effective against melanoma cells. Particularly, PTGS2 is frequently expressed in malignant melanomas and its expression significantly correlates with poor survival in patients. In this study we investigated on the effect of ptgs2 knockdown in B16F10 murine melanoma cells. Our results show that reduced expression of ptgs2 in melanoma cells: i) inhibits cell proliferation, migration, and invasiveness; ii) modulates immune response by impairing myeloid derived suppressor cell differentiation; iii) reduces tumor development and metastasis in vivo. Collectively, these findings indicate that ptgs2 could represent an ideal gene to be targeted to improve success rates in the development of new and highly selective drugs for melanoma treatment.